Quantification of Brønsted Acid Sites of Grafted Amorphous Silica–Alumina Compounds and their Turnover Frequency in m‐Xylene Isomerization. Issue 12 (15th October 2013) - Caillot, Maxime; Chaumonnot, Alexandra; Digne, Mathieu; Bokhoven, Jeroen A. Van
Abstract The number and types of acid sites and the catalytic activity of amorphous silica–alumina, obtained by grafting silicon species to the surface of γ‐alumina, varies with the synthesis conditions and the amount of grafted silicon. IR spectroscopy of the OH region proves that deposition occurs selectively, first on the (1 0 0) and then on the (1 1 0) facets. Grafting onto the (1 0 0) surface lowers the number of active sites in ethanol dehydration. Grafting onto the (1 1 0) surface yields Brønsted acid sites that are active in the dehydration of ethanol and that catalyze the isomerization of m‐xylene. Strong Lewis acid sites, or "defect sites", as detected by CO adsorption, also appear, although they are absent on the parent alumina. The stoichiometric dehydration of ethanol on Brønsted sites, monitored by using thermogravimetric analysis, enables the calculation of the turnover frequency of these sites in m‐xylene isomerization (1.4×10−3 s−1 site−1 at 350 °C, atmospheric pressure, 0.6 cm3 h−1 of m‐xylene, and 0.5 g of catalyst). This number is 22 times lower than on a USY zeolite without extraframework aluminum.